Communication aid provision and use among children and adolescents developing aided communication: an international survey - von Tetzchner, Stephen; Launonen, Kaisa; Batorowicz, Beata; Nunes, Leila Regina d’Oliveira de Paula; Walter, Cátia Crivelenti de Figueiredo; Oxley, Judith; Massaro, Munique; Stadskleiv, Kristine; Yang, Chih-Kang; Deliberato, Débora [UNESP] (Taylor & Francis, 2018)
A fundamental requirement of a supportive language development for young children who need aided communication is that an aided communication system is made available and its use is supported. There is limited information about the age at which children are typically provided with a communication aid or about how aided communication is used in everyday situations. Using questionnaire-based interview data, this study investigated (a) the pattern of provision of communication aids to 84 children and adolescents, (b) parents’ and professionals’ evaluation of the quality of communication across contexts, and (c) availability and use of aided communication in these contexts. The age at which the participants received their first aided system varied considerably across the group; however, most were considerably older than the age at which children with typical development usually begin to speak. Parents and professionals rated most everyday situations as good communication situations but reported that the participants did not have their main form of expressive language available in many of these situations, or did not use it much. Parents rated their child’s education in relation to aided language positively, but many professionals indicated that they had limited knowledge about the participant’s use of aided communication outside of the school environment, or about the parents’ attitudes. The study gives insights into the language learning situation of children and adolescents who develop aided communication.
Keywords: Communication aids; development; language environments; parent perspectives; professional perspectives